Effects of nitrogen fertilization on lettuce (Lactuca sativa) crop in Pedro Carbo canton, Guayas province - Vargas Guillén, Pablo Israel; Alejandro Beltrán, Bryan Alberto; Centanaro Quiróz, Paulo Humberto; Valverde Medina, Luzmila María (SATHIRI, 2023)
Nitrogen fertilization in lettuce cultivation complements the integral fertilization process, contributing to optimal and self-sustaining growth of the plant. The objective of this essay is to opt for nitrogenous fertilization alternatives that allow increasing the yield of the plant, for which different techniques and methodologies were applied, the same ones that were evaluated in their agronomic behavior, according to the study variables, contrasting these results with the economic analysis of the treatments under study through the Benefit-Cost relationship. In the development of the investigation, a completely randomized block design was used, evaluating three treatments: Treatment 1 (Urea), Treatment 2 (Micro-azot), Treatment 3 (Absolute Witness), replicated in five repetitions forming a total of fifteen experimental plots; each plot consists of nine square meters, in which the following were evaluated: plant height, days to harvest, diameter and number of commercial lettuces, lettuce weight (kg/plots), yield kg/ha, this being the most important variable , where it is concluded that the highest yield was obtained with the application of a nitrogenous fertilization (Urea). The best benefit/cost ratio resulted in treatment T1 (Urea) with 1.50 %, obtaining a net benefit of $3523.05, concluding that T1 (urea) is shown as the experiment that obtained the best results in the study zone; however, T1 and T2 do not present significant statistical differences, in contrast to T3; and with the exception of the variable "Days of harvest", in which said divergences were presented, between T1 and T2.
Keywords: Fertilization; Lettuce; Nitrogenated; Yield